Evaluation of the Pediatric Bacterial Meningitis Surveillance System at Harare Hospital 2015 - Tsikira, T.; Manangazira, P.; Mungati, M.; D, Bangure; N, Gombe; *, Tshumanga (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Paediatric Bacterial Meningitis Surveillance was launched by the World Health Organisation in 2002 at Harare Central Hospital. An Evaluation of the surveillance system at this site was carried out because the site had a poor reporting rate of 13,3% in 2013, there was 50% completeness of the reported cases and there was also 0% culture positivity for Hib against a set target of 20%. Methods A descriptive cross sectional study was conducted using the CDC guidelines for evaluating a surveillance system. Results 27 of the 30 health care workers involved in PBM were interviewed. Only 27,6% were aware of the reporting deadlines and 22% had ever notified a case. 63% of the participants thought the system was too long taking at least 30 minutes to fill in.